REKONSILIASI FISKAL PADA PT. KARYA INSAN SATU NAMA DI SAMARINDA - Imam Nazarudin Latif, Muhammad Yatim, H. Eddy Soegiarto K, (EKONOMIA, 2015)
The aim of this study was to determine differences in income and expenses based Standar Akuntansi Keuangan (SAK) and Tax Law, calculating the reconciliation to the financial statements so that it can be used as a commercial bases of corporate income tax in accordance with the provisions of Tax Law. Basic theory used is the Law for Corporate Income Tax. The hypothesis raised is